(untitled) - Barrett, C. K.; (2017-2021) (Philadelphia, U.S.A, 1982)
`In this outstanding collection, eminent New Testament scholar C. K. Barrett considers various dimensions of the fourth gospel. As a foundation for greater understanding, he discusses the theological method inherent in John's writings. He includes an important chapter on Christology that deals with Jesus' relationship to God and the nature of his humanness. Particularly revealing is the comparison of the theological vocabulary of the Gospel of John and the Gospel of Truth. Four vital aspects of Johannine literature are discusses : symbolism, sacraments, paradox-dualism, and history. One essay is devoted to Ignatius of Antioch, whose thought is related to John's.`
Keywords: Bible -- New Testament -- Jean -- Critique, interprétation, etc